Organic farming in India: Production, export, certification and policy support - MALIK, D P (The Indian Journal of Agricultural Sciences, 2020)
Organic farming has the potential to provide benefits in terms of environmental protection, conservation of nonrenewable resources and improved food quality. The paper attempts to study production status, export potential and policy support for products cultivated organically in India. The information was gathered from various published sources and descriptive analysis to draw valid inferences. The area, production and export figures divulge that crops are grown organically to meet rising demand of organic products in abroad. Recently PGS low cost certification was introduced for the sale of organic products in domestic markets. Various initiatives like arrangement of quality seed and planting material, capacity building, creation of infrastructure, marketing, processing etc. have been taken to support organic farming in India.